Development of a Web-Based Survey for Monitoring Daily Health and its Application in an Epidemiological Survey - Sugiura, Hiroaki; Ohkusa, Yasushi; Akahane, Manabu; Sano, Tomomi; Okabe, Nobuhiko; Imamura, Tomoaki (JMIR Publications, 2011)
BackgroundEarly detection of symptoms arising from exposure to pathogens, harmful substances, or environmental changes is required for timely intervention. The administration of Web-based questionnaires is a potential method for collecting information from a sample population. ObjectiveThe objective of our study was to develop a Web-based daily questionnaire for health (WDQH) for symptomatic surveillance. MethodsWe adopted two different survey methods to develop the WDQH: an Internet panel survey, which included participants already registered with an Internet survey company, and the Tokyo Consumers' Co-operative Union (TCCU) Internet survey, in cooperation with the Japanese Consumers' Co-operative Union, which recruited participants by website advertising. The Internet panel survey participants were given a fee every day for providing answers, and the survey was repeated twice with modified surveys and collection methods: Internet Panel Survey I was conducted every day, and Internet Panel Survey II was conducted every 3 days to reduce costs. We examined whether the survey remained valid by reporting health conditions on day 1 over a 3-day period, and whether the response rate would vary among groups with different incentives. In the TCCU survey, participants were given a fee only for initially registering, and health information was provided in return for survey completion. The WDQH included the demographic details of participants and prompted them to answer questions about the presence of various symptoms by email. Health information collected by the WDQH was then used for the syndromic surveillance of infection. ResultsResponse rates averaged 47.3% for Internet Panel Survey I, 42.7% for Internet Panel Survey II, and 40.1% for the TCCU survey. During a seasonal influenza epidemic, the WDQH detected a rapid increase in the number of participants with fever through the early aberration reporting system. ConclusionsWe developed a health observation method based on self-reporting by participants via the Internet. We validated the usefulness of the WDQH by its practical use in syndromic surveillance.